Changes in carbon sequestration with age of trees in guava orchards at different locations in a tropical climate on Alfisols - Bijay, B K; Ganeshamurthy, A N; Abhiram, D; Dibya, K S; Rupa, T R; Subash, S C; Gobinda, A C; Sipra, M (Plant Science Today, 2025)
Understanding changes in carbon (C) fluxes resulting from land-use change patterns is essential for formulating effective climate change mitigation strategies. This study conducted at two different locations focuses on the dynamics of carbon sequestration in guava orchards as a function of tree age, a land-use type that is increasingly prevalent in agricultural regions. Through comprehensive sampling in different agro-climatic zones, the carbon content stored in tree biomass, litter, weeds and soil layers was assessed, the evaluation of which provided insights into carbon levels in different environmental contexts. Carbon sequestration was observed to increase with guava orchard age, with mean carbon stocks of 106.84 t C/ha in Dhenkanal and 114.35 t C/ha in Rayagada. In guava orchards aboveground carbon accounted for 21.22% and 22.38% of total carbon sequestered per hectare at the recommended spacing of 6 × 6 m in Dhenkanal and Rayagada, respectively. Our findings provide critical baseline data on carbon stocks in guava orchards as a function of tree age, contributing to the understanding of the carbon cycle in these cultivated ecosystems. This study highlights the importance of region-specific data, and suggests future research to include guava orchards in other regions with larger sample sizes to comprehensively assess carbon sequestration potential nationwide.